Datos sobre la Vitamina E - Jennifer Hillan (EDIS)
FCS8641-Span, a 2-page fact sheet by Jennifer Hillan, is the Spanish version of "Facts about Vitamin E" (FCS8641). It explains the importance of vitamin E in our diets, how much we need, and how to get this vital nutrient. Published by the UF Department of Family, Youth, and Community Sciences, June 2007.